2018
DOI: 10.1055/s-0038-1636520
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Artery Embolization for Treatment of Postpartum Hemorrhage

Abstract: Postpartum hemorrhage (PPH) is the leading cause of maternal perinatal morbidity and mortality worldwide. Defined as greater than 500 mL blood loss after vaginal delivery, and greater than 1,000 mL blood loss after cesarean delivery, PPH has many causes, including uterine atony, lower genital tract lacerations, coagulopathy, and placental anomalies. Correction of coagulopathy and identification of the cause of bleeding are mainstays of treatment. Medical therapies such as uterotonics, balloon tamponade, pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 88 publications
0
8
0
1
Order By: Relevance
“…Only 3 of them were less than gestational age. 53 These numerical values indicated that PAE has no direct effect on the placental blood supply and fetal growth. The formation of collateral circulation develops very quickly after PAE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only 3 of them were less than gestational age. 53 These numerical values indicated that PAE has no direct effect on the placental blood supply and fetal growth. The formation of collateral circulation develops very quickly after PAE.…”
Section: Discussionmentioning
confidence: 98%
“…The current literature suggests using a diameter of 500 to 1000 μm gelatin sponge granules for embolization in PPH. 16 , 53 Other embolic agents are used less often. Hemostasis of NBCA is based on the mechanism of rapid polymerization and hardening in an ionic fluid without abundant clotting factor.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been validated by some other authors, too [13, 16, 17]. In cases with unsuccessful attempts of intraoperative bleeding control, intraoperative or postoperative embolization may be the procedure of choice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive factors associated with an unsuccessful UAE in PPH encompass DIC, blood transfusion of 5—10 units, blood loss > 1.5L, pronounced arterial vasoconstriction during embolization procedure and unilateral UAE [ 25 ].…”
Section: Primary and Secondary Postpartum Hemorraghementioning
confidence: 99%
“…UAE in PPH is predominantly carried out employing non-permanent embolic materials such as resorbable gelatine sponge (GS) [ 20 , 31 ]. GS expedite swift hemostasis by inducing mechanical obstruction and promoting thrombus formation within the vessel lumen which recanalizes in approximately 3 to 6 weeks [ 25 ]. The preparation of GS for embolization involved the creation of small torpedoes or a semi-liquid form from 1-2 mm pledgets (“slurry”).…”
Section: Primary and Secondary Postpartum Hemorraghementioning
confidence: 99%